JEJAK SEJARAH PERGESERAN IDENTITAS AGAMIS MENJADI PUB-KULTUR DI PATI - Fathimatuz Zahra (UIN Raden Mas Said Surakarta, 2018)
This study attempts to describe historical trace of the shifting community identity in region of Pati, Central Java; from religious identity to pub-culture (karaoke culture). Based on the qualitative approach, wherein the data gathered through an interview to the selected local leaders and observation conducted through various archeological remains and documents, this study revealed that the shifting identity happened basically was not a new thing. Based on the folklore believed by local community, story of Mbah Cungkrung, the first famous Islamic carrier and preacher, Pati has well known as the religious city. While from Babad Randukuning, the story of tayub dancer struggle called â€œRondho Kuningâ€, the first women who built dance community although initially opposed by the Duke at that time, religious identity has shifted toward pub-culture. Although religious identity was not completely disappeared; the existence of some Pesantrens till nowadays as its evidence, but growing identity of pub-culture recently; the wide spreading culture of kethoprak and karaoke also used as its historical evidence.